224k views
0 votes
If 3(x - 4) = x + 4, then x =8

If 3(x - 4) = x + 4, then x =8-example-1
User Elgehelge
by
7.3k points

2 Answers

7 votes

Answer:

Valid

Explanation:

3(x-4)=x+4 Given

3x-12=x+4 Distribute

2x=16 Subtract x from both sides and add 12 to both sides

x=8 Divide each side by 2.

User Thsorens
by
7.9k points
5 votes

Hey there!

3(x - 4) = x + 4

3(x) + 3(-4) = x + 4

3x - 12 = x + 4

3(8) - 12 = 8 + 4

24 - 12 = 8 + 4

12 = 12

Therefore, this makes this statement TRUE

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

User Julius
by
6.9k points